Effectiveness of Alpha-toxin Fab Monoclonal Antibody Therapy in Limiting the Pathology of Staphylococcus aureus Keratitis. (August 2015) - Caballero, Armando R.; Foletti, Davide L.; Bierdeman, Michael A.; Tang, Aihua; Arana, Angela M.; Hasa-Moreno, Adela; Sangalang, Emma Ruth B.; O'Callaghan, Richard J.
Abstract Purpose: To investigate the effectiveness of a high-affinity human monoclonal antibody Fab fragment to Staphylococcus aureus alpha-toxin (LTM14 Fab) as therapy for S. aureus keratitis. Methods: A single topical drop of the LTM14 Fab antibody to alpha-toxin alone, or in 0.006% benzalkonium chloride (BAK), was applied every 30 min to S. aureus-infected rabbit corneas from 9 to 14 hours post-infection. Erosions and pathology were measured at 15 h post-infection. Results: LTM14 Fab with BAK limited corneal erosions better than LTM14 Fab alone (p = 0.036), and both limited erosions compared to untreated eyes (p ≤ 0.0001). Overall pathology was similar in all groups (p ≥ 0.070), but iritis and chemosis were reduced by treatment (p ≤ 0.036). Conclusions: The high-affinity human monoclonal Fab fragment antibody (LTM14 Fab) to S. aureus alpha-toxin was effective in reducing corneal damage during S. aureus keratitis.